Efficiency of the Use of QRIS on Increasing Sales at Le Garden Palembang Indah Mall - Salim, Amir; Nofiansyah, Doly (Institut Agama Islam (IAI) SEBI, 2023)
ABSTRACT The rapid development of technology and information in various digital markets, marketplaces, or platforms which provides space for SMEs to market their products, and reach various geographical areas in Indonesia and abroad. In realizing safe, easy, and efficient payments in the digital era, Bank Indonesia and the Indonesian Payment System Association (ASPI) continue to improve and develop the QRIS payment system to increase the efficiency of non-cash payment system services. This study aims to determine the practice of using Quick Response Code Indonesia Standard (QRIS) in increasing sales to MSMEs at Le Garden Palembang Indah Mall and to analyze the usage efficiencyQuick Response Code Indonesia (QRIS) on increasing sales to MSMEs at Le Garden Palembang Indah Mall. This research uses quantitative research and data collection techniques in the form of observation, interviews, questionnaires, and documentation. Participants in this study totaled 38 SMEs at Le Garden Palembang Indah Mall. Determination of informants using saturated sampling techniques and incidental sampling. Based on the results of research that (1) the practice of using Quick Response Code Indonesia (QRIS) to increase sales to MSMEs at Le Garden Palembang Indah Mall begins with the buyer telling the employee to make a non-cash payment, the employee will direct the buyer to scan the QR Code then type in the nominal amount to be paid, then the buyer's balance will automatically decrease. (2) efficiency of using Quick Response Code Indonesia (QRIS) on increasing sales to MSMEs at Le Garden Palembang Indah Mall refers to the measurement of results (output) and input Those who accept the existence of QRIS are satisfied, so transactions do not take a long time, make it easier and more efficient. In addition, the results obtained from the validity test rcount rtable(0.339 0.320) is declared valid, while the reliability test that rcount rtable(0.5063 0.320) is stated to be reliable, so it can be concluded that the use of QRIS is very efficient.